My try, using $x = \sec(u)$ substitution:

$$ \begin{eqnarray} \int \frac{\sqrt{x^2-1}}{x} \mathrm{d}x &=& \int \frac{\sqrt{\sec^2(u) - 1}}{\sec(u)}\tan(u)\sec(u) \mathrm{d}u \\ &=& \int \tan^2(u) \mathrm{d}u \\ &=& \tan(u) - u + C \\ &=& \tan(arcsec(x)) - arcsec(x) + C \end{eqnarray} $$

However, according to Wolfram Alpha, the answer should be: $$ \int \frac{\sqrt{x^2-1}}{x} \mathrm{d}x = \sqrt{x^2-1}+\arctan \left( \frac{1}{\sqrt{x^2-1}} \right)+C $$ When I derive this last answer I don't get back the integrand, but rather: $$ \frac{\mathrm d}{\mathrm d x}\left(\sqrt{x^2-1}+\arctan \left( \frac{1}{\sqrt{x^2-1}} \right)+C\right) = \frac{x}{\sqrt{x^2-1}}- \frac{x}{(x^2-1)^{3/2}\left(1+\frac{1}{x^2-1}\right)} $$

I don't know how to simplify this expression more. Also, I am unable to check whether my answer is correct because I don't know how to find the derivative of $arcsec(x)$.

Can someone check my calculations and tell me where I've done something wrong and how one can simplify the last expression to get back the integrand?

  • 2
    $\begingroup$ I know it is not your main question, but here is a good way to find the derivatives of the inverse trig functions if you ever don't know them. If $y=\sec^{-1} x$ then $x=\sec y$, and by implicit differentiation we fine $1=\sec y\tan y\frac{dy}{dx}\implies\frac{dy}{dx}=\frac{1}{\sec y\tan y}$. $\sec\sec^{-1} x=|x|$ and $\tan\sec^{-1} x=\sqrt{x^2-1}$. Therefore, the derivative of $\sec^{-1} x$ is $\frac{1}{|x|\sqrt{x^2-1}}$. Now you can check your answer. It is probably correct too. $\endgroup$ – solstafir Apr 16 '14 at 23:20
  • 1
    $\begingroup$ Related math.stackexchange.com/questions/153553/… $\endgroup$ – user85798 Apr 16 '14 at 23:22
  • $\begingroup$ @solstafir Why is $\sec(arcsec(x)) = |x|$ with the absolute value? $\endgroup$ – hallaplay835 Apr 17 '14 at 12:36
  • 1
    $\begingroup$ Sorry for the confusion. In general, $\sec\sec^{-1} x$ is not always positive. You have to use the absolute value here because of the $\tan y$. This is because $\sec y = \frac{1}{\cos y}$ and $\tan y = \frac{\sin y}{\cos y}$. For $y \in [0,\pi]$ (the range of $\sec^{-1} x$), $\sin y$ is always positive, but $\cos y$ is negative for $x \in (\frac{\pi}{2},\pi]$. But $\sec y$ and $\tan y$ are being multiplied, so the negatives cancel and the product is always positive. But in $\tan\sec^{-1} x=\sqrt{x^2-1}$ we always take the positive square root. $\sec\sec^{-1} x=|x|$ corrects for this. $\endgroup$ – solstafir Apr 17 '14 at 17:25
  • $\begingroup$ See also: Evaluating $\int\frac{\sqrt{x^2-1}}x\mathrm dx$ $\endgroup$ – Martin Sleziak Aug 17 '18 at 13:24

arcsec$(x)$ is the angle whose secant is $x$. I'm guessing you may be more familiar with the derivative of inverse cosine. The angle that has a secant of $x$ has a cosine of $\frac1x$.

Also, your answer is more or less the same, just in a different form. Draw a right triangle and call one of the acute angles $A$. Secant is $\frac{\text{hypoteneuse}}{\text{adjacent}}$. If the length of the hypoteneuse is $x$ and the length of the side adjacent to $A$ is $1$, then $\sec(A)=x$. By the Pythagorean Theorem, the other leg has length $\sqrt{x^2-1}$. From this triangle, we get $\tan(A)=\tan(\sec^{-1}x)=\sqrt{x^2-1}$.

  • $\begingroup$ Thanks! I found this, a list of nice identities proved using similar constructions to yours. It may be useful to others. $\endgroup$ – hallaplay835 Apr 17 '14 at 12:50

$$\frac{x}{\sqrt{x^2-1}} - \frac{x}{(x^2-1)^{3/2} \left(1+\frac{1}{x^2-1}\right)} = \frac{x}{\sqrt{x^2-1}} - \frac{x}{\sqrt{x^2-1} (x^2-1+1)}$$ $$ = \frac{x}{\sqrt{x^2-1}} - \frac{x}{x^2 \sqrt{x^2-1}} = \frac{x^3 - x}{x^2 \sqrt{x^2-1}} = \frac{x (x^2-1)}{x^2 \sqrt{x^2-1}} = \frac{\sqrt{x^2-1}}{x}$$


Calculating this integral can be done in this way:

$$\int { \sqrt{x^2-a^2} \over x } dx =\int { x^2-a^2 \over x\sqrt{x^2-a^2} } dx= \int { x \over \sqrt{x^2-a^2} } dx-\int { a^2 \over x\sqrt{x^2-a^2} } dx =\sqrt{x^2-a^2}(+-)a\cdot\int {(\frac{x}{a})'\over \sqrt{1-(\frac{x}{a})^2)} } dx=\sqrt{x^2-a^2}(+-)a\cdot\arcsin(\frac{x}{a})+C.$$

  • $\begingroup$ Isn't $\int \frac{x^2-a^2}{x\sqrt{x^2-a^2}}\mathrm{d}x = \int \frac{x}{\sqrt{x^2-a^2}}\mathrm{d}x - \int \frac{a^2}{x\sqrt{x^2-a^2}}\mathrm{d}x$ ? Using $x = a\sec(u)$ substitution I get $\int \frac{x^2-a^2}{x}\mathrm{d}x = \sqrt{x^2-a^2} - aarcsec(\frac{x}{a}) + C$ $\endgroup$ – hallaplay835 Apr 17 '14 at 12:20
  • $\begingroup$ OK! I corrected. Thank you! $\endgroup$ – medicu Apr 17 '14 at 13:06

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.